El perfil psicológico de un asesino serial en la ciudad de Medellín (2009)
The goal of this research is to show an analysis of the psychological and forensic assessment carried out to a serial killer in the city of Medellin. In it, some historical aspects of the serial killer are made, including his characteristics and different types; as well as a description of the crimes, the killer's modus operandi and his assessment and personality profile. All of this is framed in the respect and the ethics, since this research does not attempt to judge the murder, but to analyze the phenomenon of his psychotic personality taking into account the diverse factors, which are interrelated.